Honoring Diverse Cultures Through Family Literacy Approaches That Build Family, School, and Community Partnerships. (30th January 2023) - Miller, Gloria E.; Khatib, Sara M.
Abstract: Families play a critical role in promoting students' literacy development. Family literacy practices refer to oral, written, and reading strategies that impart cultural traditions and knowledge of the world and that occur in the dominant or native language of a family. It is especially important for educators to understand and build upon such practices when working with multilingual, immigrant, refugee, or asylee students who are the first in their family to attend school in a new host country. Unfortunately, teachers frequently report they are at a loss as to how to engage with the adult guardians of these students on joint efforts to encourage reading in a second language. In this review, effective family literacy programs published in the last several decades reported in the U.S. or internationally are analyzed for how they promote early English literacy skills while honoring a family's native language and culture and simultaneously encouraging strong partnerships between homes, schools, and communities. Culturally sustaining pedagogical approaches reflected within these programs provide ideas for how to intentionally encourage future enhancements of family literacy programming and research.